Organized Crime as a Transnational Threat in the Modern Period - Dzneladze, Levan (Journal of Law, 2025)
The paper addresses one of the primary challenges of the modern era: both nationally and internationally organized crime and the threats it poses. Effectively combating crimes of this nature is the primary legal obligation of any democratic state, and at this juncture, it remains an unresolved issue, which undoubtedly highlights the significance of the research. The article is based on an analysis of doctrine, legislation, and judicial practice. It reviews the main provisions of organized and transnational organized crime, as well as the existing challenges. This study aims to identify effective measures for combating organized crime and transnational organized crime, as well as to address relevant issues.